Destabilizing momentum trading and counterbalancing contrarian strategy by large trader groups. Issue 1 (19th September 2019) - Cho, Jang Hyung; Daigler, Robert; Ki, YoungHa; Zaima, Janis
Abstract : Purpose: The purpose of this paper is to assess trading strategies adopted by each large trader group and examine their effects on the volatility in the interest rate futures markets. Design/methodology/approach: The Grinblatt et al. 's (1995 ) measure of momentum strategy is used to estimate the degree momentum and contrarian strategies. Then, regression analysis is used to determine the effects of trading strategies on volatility. Findings: Up until 2005, the trades by non-clearing member firms in the futures market were separated from institutional traders providing us the opportunity to study trading strategies adopted by large distinct trading groups and its effects on volatility in the futures markets. It is found that individual traders use momentum strategy, whereas market makers and institutional traders use contrarian strategy. Momentum strategy adopted by individual traders increases volatility whereas contrarian strategy dampens volatility. Moreover, it is found that institutional traders engage more actively in contrarian trading when individual traders cause excessive volatility. The two distinct trading groups were separately tracked prior to 2005 giving us a unique window to determine the effect of the traders that conduct momentum trading as opposed to the ones that are contrarian traders. After the reclassification, the institutional trading group exhibited weaker contrarian strategy which can be attributed to the inclusion of non-clearing firm traders. Originality/value: This study documents the first empirical evidence that shows off-exchange futures trader group is not composed of only pure noise makers, but there are short-term forecasters in its group. The authors also show a unique finding that noises caused by off-exchange group is from momentum strategy that they use, whereas contrarian strategy is used by institutional trader lower volatility.